Gastrointestinal stromal tumors: advances in molecular characterization and therapeutic implications - Nildevande Firmino Lima-Jr; Marcello Moro Queiroz; Julia Sousa Leal Franco; Domingos Savio do Rego Lins-Junior; Eduardo Felício de Campos; Beatriz Mendes Awni; Luiz Guilherme Cernaglia Aureliano de Lima; Frederico Teixeira; Fábio de Oliveira Ferreira; Eduardo Hiroshi Akaishi; Fernanda Cunha Capareli; Rodrigo Ramella Munhoz (Brazilian Journal of Oncology)
Recognition of the molecular basis of gastrointestinal stromal tumors has paved the way for significant breakthroughs in the diagnosis and treatment of this disease as well as positioned gastrointestinal stromal tumors as a framework for the concept of precision oncology in solid tumors. The incorporation of novel targeted agents for molecularly defined subgroups has led to significant improvements in treatment outcomes; however, the characterization of heterogeneous KIT or PDGFRA mutations and the emergence of resistance mechanisms highlight the need for a broader use of comprehensive molecular profiling and emphasize the importance of molecularly driven adaptive treatment strategies. Such a molecular background is critical for developing personalized and effective interventions and optimizing outcomes. The present review summarizes key studies that provide the basis for standard-of-care management options as well as provides molecular insights into the management of gastrointestinal stromal tumors, with an emphasis on recent advances.